2010
DOI: 10.3126/botor.v6i0.2916
|View full text |Cite
|
Sign up to set email alerts
|

GIS/Remote sensing techniques for resource management and biodiversity protection in mountainous regions

Abstract: Biodiversity protection in mountainous regions requires effective fact-driven resource management techniques. Geoinformatic tools including GIS and remote sensing can be integrated to provide regional-scale data products across time for use in strategic and management level policymaking. Several principles are discussed to ensure that geoinformatics data and analysis can effectively contribute to resource management by clarifying issues and minimizing misinterpretation. A case study in the Chilean Andes elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Overall comparison among different forest types NDVI is highly sensitive to both canopy foliar and understory chlorophyll content (Dawson et al 2003) and is a reflection of vegetative productivity. Natural systems with more water availability are generally more robust (All 2009). Our analysis revealed that Picea-Tsuga forest had the highest NDVI values among the forests studied.…”
Section: B)mentioning
confidence: 65%
“…Overall comparison among different forest types NDVI is highly sensitive to both canopy foliar and understory chlorophyll content (Dawson et al 2003) and is a reflection of vegetative productivity. Natural systems with more water availability are generally more robust (All 2009). Our analysis revealed that Picea-Tsuga forest had the highest NDVI values among the forests studied.…”
Section: B)mentioning
confidence: 65%